ความสามารถในการสื่อสารของผู้หญิงในส่วนราชการที่เข้าร่วมโครงการส่งเสริมประสิทธิภาพของสำนักงาน ก.พ. - ผานิต อมราพิทักษ์ (จุฬาลงกรณ์มหาวิทยาลัย, 2001)
The present survey research was conducted in attempts to study Thai women s work roles and status and factors affecting the acceptance of their work competence. In addition, the study investigated the characteristics of communicatively competent and incompetent Thai working women. Questionnaire data (N=252) were collected from 5 government offices participating in OCSC s Public Performance Improvement Project (i.e., the Department of Commercial Registration, the Department of Revenue, the Department of Lands, the Office of Civil Service Commission, and the Office of Social Security). The study results indicated that : 1. Today Thai women gain more acceptance in work roles and status than before. Moreover, Thai organizations provide more opportunities for women to demonstrate their work competence equally to men. 2. The factors which affected the acceptance of women s work roles and status in government offices were the levels of English competency and computer literacy, age, length of work experience and educational background. 3. The characteristics of communicatively competent female superiors were such as ability to work with a team, ability to pass on knowledge with a clear and systematic manner, ability to give suggestions to subordinates and to help solve their subordinates problems. The characteristics of communicatively competent female subordinates were such as, ability to pass on knowledge with a clear and systematic manner, ability to follow organizational rules, regulations and policies, ability to work with a team, ability to make clear and interesting presentations on their work, and ability to speak with polite and respectful manners. The characteristics of communicatively competent female co-workers were such as ability to provide supports for others and save their co-workers faces when coping with work problems, ability to pass on knowledge with a clear and systematic manner and ability to assertively express candid opinions. 4. Communicatively incompetent female superiors were found to do anything to get what they want, to often criticize others mistake, and to speak in inconsiderate, sarcastic and nonpersuasive manners. Communicatively incompetent female subordinates spoke along with their superiors with nonrational ingratiating manners, had no knowledge on what they talked about, and took credits from others ideas. Communicatively incompetent female co-workers often criticized others mistakes, spoke in inconsiderate and nonpersuasive styles, and expressed dissatisfaction when being assigned to work with others.